CONTENT ASPECT OF EDUCATIONAL CONTROL ACTIVITIES OF UNIVERSITY STUDENTS (Pedagogy of Higher and Secondary Education, 2008)
The semantic aspect of control of educational activity of students of higher educational establishments is examined in the article.